2017
DOI: 10.1093/rheumatology/kew507
|View full text |Cite
|
Sign up to set email alerts
|

Countermeasures against methotrexate intolerance in juvenile idiopathic arthritis instituted by parents show no effect

Abstract: MTX intolerance was present in many children with JIA and symptoms decreased little in the short term. Various modalities used as countermeasures against nausea by parents showed no discernible effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
3
4
0
Order By: Relevance
“…This may contribute to the high number of MTX intolerant children in our JIA group. Especially, when studies have shown that MTX intolerance develops within the first year of low-dose MTX treatment and stays rather stable over time [7,16,18]. However, the duration of low-dose MTX treatment in our JIA group is comparable to the study by Scheuern et al [7] finding a lower proportion of MTX intolerant patients with JIA.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This may contribute to the high number of MTX intolerant children in our JIA group. Especially, when studies have shown that MTX intolerance develops within the first year of low-dose MTX treatment and stays rather stable over time [7,16,18]. However, the duration of low-dose MTX treatment in our JIA group is comparable to the study by Scheuern et al [7] finding a lower proportion of MTX intolerant patients with JIA.…”
Section: Discussionsupporting
confidence: 77%
“…Especially, when studies have shown that MTX intolerance develops within the first year of low-dose MTX treatment and stays rather stable over time [7,16,18]. However, the duration of low-dose MTX treatment in our JIA group is comparable to the study by Scheuern et al [7] finding a lower proportion of MTX intolerant patients with JIA. Additionally, in our study the median duration of low-dose MTX treatment was the same in the JIA subgroup of MTX tolerant patients as in the JIA subgroup of MTX intolerant patients.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Recently two large studies on anti-emetics for MTX-intolerance in pediatric patients have been published, providing some evidence against the conclusion by Falvey et al [ 4 , 5 ]. Scheuern et al described the results of a prospective, observational study in 196 JIA patients.…”
mentioning
confidence: 99%
“…Scheuern et al described the results of a prospective, observational study in 196 JIA patients. They concluded that “various modalities used as countermeasures against nausea (…) showed no discernible effect” [ 4 ]. Dupont-Lucas et al performed an observational study in 102 pediatric IBD patients.…”
mentioning
confidence: 99%